Homeostasis of common bean populations with different genetic structures - Bruzi, Adriano Teodoro (2013)
Eight lines of common bean, a mixture in equal proportions (MP) and the F2 generation of the multiple hybrids (MH) between them were analyzed to verify whether they differ in homeostasis and phenotypic plasticity. The experiments were conducted in 20 environments (seasons and locations) from November 2004 to December 2005, in Alto Paranaíba and the south of Minas Gerais state. Based on the mean yield of the environments the stability was evaluated by the ecovalence values (Wi 2). To estimate the repeatability of the stability parameters the 20 environments were separated in two groups of 10, simulating 1000 possibilities. The MH and MP were the most stable. Nevertheless, high stability was also identified in some pure lines. The repeatability of mean grain yield (rk 2=0.73) was higher than Wi 2 (rk 2=0.18). The chances of success of selection for the smallest contribution to the G x E interaction are small.